2021
DOI: 10.1177/0361684321993796
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Disempowerment and Preferences for Skin Lightening Products That Reinforce Colorism: Experimental Evidence From India

Abstract: Global racism and colorism, the preference for fairer skin even within ethnic and racial groups, leads millions of women of African, Asian, and Latin descent to use products with chemical ingredients intended to lighten skin color. Drawing from literatures on the impact of chronic and situational disempowerment on behavioral risk-taking to enhance status, we hypothesized that activating feelings of disempowerment would increase women of color’s interest in stronger and riskier products meant to lighten skin to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…These findings prove that women feel greater cultural associations that are linked with fair skin (Chen and Francis-Tan 2021). In the Indian caste system, dark skin is associated with disempowered caste (lower caste) (Adbi et al 2021). Women tend to remove disempowerment associated with dark skin so that they can improve their social status and well-being (Banerjee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings prove that women feel greater cultural associations that are linked with fair skin (Chen and Francis-Tan 2021). In the Indian caste system, dark skin is associated with disempowered caste (lower caste) (Adbi et al 2021). Women tend to remove disempowerment associated with dark skin so that they can improve their social status and well-being (Banerjee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Past scholars have opined that the superiority of fair skin lies in the Indian caste system, reinforcing the notion that higher caste individuals are fairer and lower caste individuals are darker (Shankar and Subish 2016). The inability of dark-skinned men and women to capitalise on these benefits leads to insecurities compelling them to buy skin-lightening products (Adbi et al 2021;Uzogara et al 2014). Past scholars have suggested that individuals' buying of skin-lightening creams is motivated by intrinsic factors like overcoming the feeling of low esteem and lack of confidence (Shroff et al 2018) and extrinsic factors like social pressure to look fair and higher salaried jobs and higher social status associated with fair skin (Nash et al 2006;Ajitha and Sivakumar 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a strong preference for light skin tones in today's society which can be seen in media, such as advertisements and social media throughout the world (Dixon & Telles, 2017). Various studies (e.g., Adbi et al, 2021;strmic-pawl et al, 2021;Thomas et al, 2011;Vijaya, 2019;Wallace et al, 2011) have been conducted to analyze the societal beauty standards and the impact of those standards in several countries and nations (e.g., Japan, United States, India, several Middle Eastern countries, Jamaica, and several African countries).…”
Section: Colorismmentioning
confidence: 99%
“…This is an important issue that is global; every nationality is negatively impacted by the effects of colorism (Howard, 2011;Quiros & Dawson, 2013;strmic-pawl et al, 2021). This is seen in social media and excessive skin bleaching (Adbi et al, 2021;Duke & Berry, 2011;strmicpawl et al, 2021;Vijaya, 2019). Our work investigates the experiences that young African American women report (i.e., perceived discrimination in various spheres of life, including health care settings) as a function of their actual and perceived skin tone.…”
mentioning
confidence: 99%